The Prevalence and Correlative Factors of Depression Among Chinese Teachers During the COVID-19 Outbreak - Zhou, Jiaojiao; Yuan, Xiaofei; Huang, Huanhuan; Li, Yaqiong; Yu, HongYe; Chen, Xu; Luo, Jia (Frontiers in Psychiatry, 2021)
Background: Epidemiological data on outbreak-associated depression of Chinese teachers are not available. This study aimed to investigate the prevalence and correlates of depression among teachers during the coronavirus disease 2019 (COVID-19) outbreak in mainland China. Methods: A large cross-sectional online survey was conducted during the COVID-19 outbreak. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9). The Connor-Davidson Resilience Scale 25 (CD-RISC 25) and Perceived Stress Scale-10 (PSS-10) were used to measure the mental resilience and stress of participants. The correlative factors of depression were analyzed. Results: In this study, 1,096 teachers were analyzed with a median (range) age of 41 (20–65) years. Of them, 624 (56.9%) suffered from depression (PHQ-9 total score of >4). The multivariate analyses showed that participants with aged ≥41 years (OR = 0.752, 95% CI:0.578–0.979, p = 0.034), participating in epidemic prevention and control (OR = 1.413, 95% CI:1.070–1.867, p = 0.015), thinking prolonged school closure have bad effect (OR = 1.385, 95% CI:1.017–1.885, p = 0.038), sleep duration/day of <6 hours (OR = 1.814, 95% CI:1.240–2.655, p < 0.001), physical exercise duration/day of <30 minutes (OR = 1.619, 95% CI:1.247–2.103, p < 0.001), spending less time with family (OR = 1.729, 95% CI: 1.063–2.655, p = 0.002), being concerned about COVID-19 (OR = 0.609, 95% CI:0.434–0.856, p = 0.004), having poor mental resilience (OR = 6.570, 95% CI:3.533–12.22, p < 0.001) and higher PSS-10 scores (OR = 9.058, 95% CI:3.817–21.50, p < 0.001) were independently associated with depression. Conclusion: During the COVID-19 outbreak, depression was common among teachers. Age, participating in epidemic prevention and control, opinions towards distant teaching and prolonged school closure, sleep duration/day, physical exercise duration, spending time with family, attitude toward COVID-19, mental resilience and stress represented the independent factors for suffering from depression.